The Impacts of Fears of COVID-19 on University Students’ Adaptability in Online Learning - Van, Dao Thi Hong; Khang, Nguyen Duy; Thi, Ha Hoang Quoc (Frontiers in Education, 2022)
Fears of Covid-19 covered humans on earth quickly since the first appearance of Coronavirus in Wuhan in 2019. Consequently, online learning has been deployed widely to ensure the continuity of education in the context of the pandemic. The mixed-method study was conducted to examine the extent of fears Vietnamese students’ perceived as well as their learning adaptability, using the FCV19 scale and Adaptability scale as research instruments. Data was analyzed relied on Mean statistics from SPSS22, combined with Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) to examine the influences of fears of Covid-19 on students’ online learning adaptability. The results triangulated with qualitative data from open-ended questions showed that students were moderately afraid of the Covid-19 pandemic but had a high level of adaptability in online learning. Additionally, fears of Covid-19 also had little impact on students’ online learning adaptability. Instead, students showed off some other fears preventing their virtual learning, including (1) fears of wasting time and money for a shoddy online education, (2) fears of loneliness and laziness, (3) fears of distracting factors when learning online, and (4) fears of lacking learning materials.